ChemInform Abstract: Magnetic Structure of the Magnetocaloric Compound AlFe2B2. Issue 17 (April 2016) - Cedervall, Johan; Andersson, Mikael Svante; Sarkar, Tapati; Delczeg‐Czirjak, Erna K.; Bergqvist, Lars; Hansen, Thomas C.; Beran, Premysl; Nordblad, Per; Sahlberg, Martin
Abstract: The crystal and magnetic structures of the title compound are investigated by powder X‐ray and neutron diffraction, magnetic measurements, and DFT electronic structure calculations.